2016
DOI: 10.1016/j.vph.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide: A novel mechanism for the vascular protection by resveratrol under oxidative stress in mouse aorta

Abstract: Reactive oxygen species (ROS) decreases bioavailability of nitric oxide (NO) and impairs NO-dependent relaxations. Like NO, hydrogen sulfide (HS) is an antioxidant and vasodilator; however, the effect of ROS on HS-induced relaxations is unknown. Here we investigated whether ROS altered the effect of HS on vascular tone in mouse aorta and determined whether resveratrol (RVT) protects it via HS. Pyrogallol induced ROS formation. It also decreased HS formation and relaxation induced by l-cysteine and in mouse aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…Although the glucose level was not significantly higher, the decreased H 2 S formation in metS group in our study suggest that the role of metabolic factors was responsible for impairment of H 2 S level rather than hyperglycaemia, as endogenous H 2 S production was significantly decreased in penile tissues or corpus cavernosum smooth muscle cell culture under hyperglycaemic conditions (Zhang et al., ). This decrease also may be due to oxidative stress, as it has previously been shown that oxidative stress leads to decrease in both basal and L‐cysteine‐stimulated H 2 S formation in aorta (Yetik‐Anacak et al., ), and it is very well known that oxidative stress plays an important role in metS and ED (Jeremy et al., ). However, we should note that although we did not measure 3‐mercaptypyruvate sulphurtransferase (MPST)‐induced H 2 S formation specifically, it is possible that H 2 S formation through this enzyme may also be impaired, as a decrease in MPST‐dependent H 2 S formation was shown in hyperglycaemia (Coletta et al., ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although the glucose level was not significantly higher, the decreased H 2 S formation in metS group in our study suggest that the role of metabolic factors was responsible for impairment of H 2 S level rather than hyperglycaemia, as endogenous H 2 S production was significantly decreased in penile tissues or corpus cavernosum smooth muscle cell culture under hyperglycaemic conditions (Zhang et al., ). This decrease also may be due to oxidative stress, as it has previously been shown that oxidative stress leads to decrease in both basal and L‐cysteine‐stimulated H 2 S formation in aorta (Yetik‐Anacak et al., ), and it is very well known that oxidative stress plays an important role in metS and ED (Jeremy et al., ). However, we should note that although we did not measure 3‐mercaptypyruvate sulphurtransferase (MPST)‐induced H 2 S formation specifically, it is possible that H 2 S formation through this enzyme may also be impaired, as a decrease in MPST‐dependent H 2 S formation was shown in hyperglycaemia (Coletta et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…showed compensatory and increased significant role of H 2 S to maintain vasorelaxation in penis in eNOS deficiency (Yetik‐Anacak et al., ). The beneficial effect of H 2 S donors on metS‐induced ED may include not only their vasodilator effects in penis but also PDE inhibition (Bucci et al., ), antioxidant (Yetik‐Anacak et al., ) and angiogenic effects as well (Papapetropoulos et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic exposure to resveratrol (50 mg/l in drinking water for 21 days) increased the production of NO and nitrite/nitrate level and decreased superoxide production in the rat aorta (Soylemez, Gurdal, Sepici, & Akar, ). Furthermore, Yetik‐Anacak, Sevin, Ozzayım, Dereli, and Ahmed () proposed vaso‐protective effects of resveratrol against oxidative stress via inducing H 2 S pathway in mouse aorta (Yetik‐Anacak et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that H 2 S has a role in the regulation of vascular tone. H 2 S induced vascular relaxation in aorta [ [78] , [79] , [80] ], gastric artery [ 81 ], mesenteric artery [ 5 , 82 ], and internal mammary artery [ 83 ]. Accumulative evidence indicate that H 2 S is an EDHF [ 5 , [17] , [18] , [19] , [20] , 82 , [84] , [85] , [86] ].…”
Section: H 2 S Is An Endothelium-derived Hyperpolamentioning
confidence: 99%